Tantangan Penerapan Prinsip Hukum Tata Negara dalam Putusan Pengadilan Agama di Indonesia - Karimah, Intan Nurul (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: Implementation of constitutional principles in Religious Court decisions in Indonesia involves several complex aspects. Religious courts play an important role in resolving family disputes and Islamic law issues, but are often influenced by various external factors that can undermine their independence. Research method used is a qualitative approach that analyzes legal documents, laws and regulations, and related court decisions. This analysis aims to identify and analyze the challenges faced in the application of constitutional principles in Religious Court decisions in Indonesia. Results from this study show that there are administrative interventions, lack of public understanding of constitutional principles and lack of human resources in the judiciary. In addition, there is the problem of harmonization of positive law and Islamic law which often causes confusion in law enforcement. Our study suggests the need to increase the capacity of judicial institutions, improve public legal education, and strengthen the principle of judicial independence. This research is expected to contribute to the development of a fairer and more transparent legal system in Indonesia.Keywords: Constitutional Law, Islamic Family Law, Religious Courts & Legal Harmonization. Abstrak: Penerapan prinsip ketatanegaraan dalam putusan Pengadilan Agama di Indonesia melibatkan beberapa aspek yang kompleks. Pengadilan agama berperan penting dalam menyelesaikan sengketa keluarga dan permasalahan hukum Islam, namun seringkali dipengaruhi oleh berbagai faktor eksternal yang dapat melemahkan independensinya. Metode penelitian yang digunakan adalah pendekatan kualitatif yang menganalisis dokumen hukum, peraturan perundang-undangan, dan keputusan pengadilan terkait. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis tantangan yang dihadapi dalam penerapan prinsip ketatanegaraan dalam putusan Pengadilan Agama di Indonesia. Hasil dari penelitian ini adanya intervensi administratif, kurangnya pemahaman masyarakat terhadap prinsip-prinsip konstitusi dan kurangnya sumber daya manusia di bidang peradilan. Selain itu, terdapat permasalahan harmonisasi hukum positif dan hukum Islam yang seringkali menimbulkan kebingungan dalam penegakan hukum. Penelitian ini diharapkan dapat memberikan kontribusi terhadap pembangunan sistem hukum di Indonesia yang lebih adil dan transparan.Kata kunci: Hukum Tata Negara, Hukum Keluarga Islam, Pengadilan Agama & Harmonisasi Hukum.